Factors influencing regular physical exercise among the elderly in residential care facilities in a South African health district - Aro, Abiodun A. (Afr J Prim Health Care Fam Med, 2018)
BACKGROUND: Physical exercise plays an important role in healthy ageing, but the elderly do not engage in it regularly. METHODS: In this cross-sectional study, we sampled 139 residents of residential care facility. A questionnaire was used to obtain information on participants’ demography, health problems, nature, motivators and barriers to exercise. Chi-square test examined the relationship between participants’ characteristics and their engagement in regular exercise. RESULTS: Of the 139 participants, the majority were females (71.9%), white people (82.7%), aged 70 years or more (70.5%), had at least one health problem (85.6%) and were overweight or obese (60.4%). Approximately 89.2% engaged in some form of physical activities but only 50.3% reported engaging regularly. Participant’s knowledge of the benefits of regular physical activities, opportunities to socialise, encouragement by health care workers and availability of exercise facilities and trainers promote regular physical exercise. Barriers to regular exercise included poor health status, lack of knowledge of the benefits of regular physical activities, lack of opportunities to socialise, lack of encouragement by health care workers and unavailability of exercise facilities and trainers. Factors that predicted exercise were age 60–69 years (p = 0.02), being Afrikaans speaking (p = 0.04) and completing high school (p = 0.03). CONCLUSION: A significant proportion of the elderly do not engage in regular physical exercise, and this behaviour is influenced by personal health status and systems-related motivators and barriers.